2021
DOI: 10.3390/biology10080795
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Functional Verification of CYP408A3 and CYP6CS3 Related to Chlorpyrifos Resistance in the Sogatella furcifera (Horváth) (Hemiptera: Delphacidae)

Abstract: The white-back planthopper (WBPH), Sogatella furcifera, mainly harms rice and occurs in most rice regions in China and Asia. With the use of chemical pesticides, S. furcifera has developed varying degrees of resistance to a variety of pesticides. In our study, a chlorpyrifos-resistant population (44.25-fold) was built through six generations of screening with a sublethal dose of chlorpyrifos (LD50) from a field population. The expression levels of ten selected resistance-related P450 genes were analyzed by RT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…13 Research on the resistance mechanism of S. f urcifera mainly focuses on enhancing insecticide metabolism mediated by overexpression of detoxification genes, such as CarE and P450. 14,15 P450 enzymes in the CYP3 clade and CYP4 clade play a crucial role in the development of metabolic resistance against insecticides. 16,17 Wang et al 18 found that the metabolic resistance of S. furcifera toward sulfoxaflor was related to the overexpression of CYP6FD1 and CYP4FD2.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Research on the resistance mechanism of S. f urcifera mainly focuses on enhancing insecticide metabolism mediated by overexpression of detoxification genes, such as CarE and P450. 14,15 P450 enzymes in the CYP3 clade and CYP4 clade play a crucial role in the development of metabolic resistance against insecticides. 16,17 Wang et al 18 found that the metabolic resistance of S. furcifera toward sulfoxaflor was related to the overexpression of CYP6FD1 and CYP4FD2.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, several other P450 enzymes have been identified as key factors in insecticide resistance, including CYP6AY1 and CYP6ER1 in Nilaparvata lugens; 19 CYP6AY3, CYP6CS3, and CYP6FJ3 in the CYP3 clade, as well as CYP417A4, CYP4DD1, and CYP4C77 in the CYP4 clade, have been found to be up-regulated and induced by imidacloprid or nitromethyleneimidazole. 20 Ruan et al 15 identified 12 potential P450 genes that may be involved in the insecticide resistance of S. furcifera, and further investigations revealed that CYP6ER4 plays a significant role in the metabolic resistance to chlorpyrifos. Pymetrozine can be hydroxylated by CYP6CM1 in Bemisia tabaci, which has conferred neonicotinoid resistance; 21 Wang et al 22 also found that the overexpression of CYP6CS1 in N. lugens was involved in resistance toward pymetrozine.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. furcifera is also a transmission vector for the southern rice black-streaked dwarf virus [18], which negatively affects rice production and leads to severe economic losses [19][20][21]. At present, S. furcifera is mainly controlled using chemical insecticides, but their excessive use not only negatively impacts the environment and natural enemies of S. furcifera, but also lead to insecticide resistance and other problems [22][23][24]. Thus, to achieve a sustainable pest management, it is imperative to find an environmentally friendly and efficient method to control S. furcifera populations.…”
Section: Introductionmentioning
confidence: 99%